2009
DOI: 10.1200/jco.2009.22.6126
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Associated Thrombosis in Patients With Malignancy

Abstract: Central venous catheters are widely used in the care of patients with cancer. Indwelling catheters are associated with upper extremity deep venous thrombosis in some patients, and recognition of this entity is an important aspect of treating patients with malignancies. This article will review the incidence, pathogenesis, clinical presentation, diagnosis, treatment, and prophylaxis of catheter-associated thrombosis in patients with malignancy. The care of pediatric patients with malignancy and catheter-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 64 publications
2
74
2
1
Order By: Relevance
“…1,6,10 This retrospective study is the first to our knowledge to determine the incidence of symptomatic UEVT in patients with cancer and identify the risk factors specifically associated with PICC-related UEVT in this population. Although previous studies have identified PICC-specific qualities that increase UEVT risk, this study also evaluated patient-specific risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6,10 This retrospective study is the first to our knowledge to determine the incidence of symptomatic UEVT in patients with cancer and identify the risk factors specifically associated with PICC-related UEVT in this population. Although previous studies have identified PICC-specific qualities that increase UEVT risk, this study also evaluated patient-specific risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of catheter-associated asymptomatic UEVT has been reported to be as high as 66%. 1,6 Although most cases are asymptomatic and of uncertain clinical significance, UEVT can have a significant impact on a patient's health care. Catheters that have lost functioning often need to be replaced at an average cost of approximately $5,000 and can lead to serious morbidity, including recurrent UEVT, postphlebitic syndrome, and pulmonary embolism.…”
Section: Introductionmentioning
confidence: 99%
“…6 Over the past 2 decades, although the use of CVCs has increased dramatically, the risk of CRTs per catheter has decreased, perhaps related to less thrombogenic catheters and improved insertion techniques. 7,8 Although the majority of asymptomatic CRT cases remain subclinical, symptomatic DVT occurs in 1%-5% of patients with a CVC (Table 1). [9][10][11][12] A prospective study of 444 cancer patients with a CVC reported symptomatic, ipsilateral DVT in 4% at a median of 30 days after insertion.…”
Section: Incidence Of Crtmentioning
confidence: 99%
“…The existing data are primarily from patients in oncological cohorts for whom the use of repeated cycles of i.v. chemotherapy requires central venous catheter placement (6)(7)(8)(9). In this population, many risk factors for thrombosis have already been identified: hypercoagulability related to prolonged bed rest during repeated hospitalizations, malnutrition, and cancer progression, particularly with metastatic disease.…”
mentioning
confidence: 99%